Analysis of Natural Convection Heat Transfer in Barapen Cooking in Papua - Numberi, Johni Jonathan; Palamba, Pither; Giai, Agustinus; Rumar, Kristofel; Joni; Ansanay, Yane; Ranteallo, Obet T.; Siregar, Samuel P.; Kaiwai, Ruben M.; Rantepulung, Selyus; Werdani, Anastasia Sri; Griapon, Nourish; Wanane, Yohanis; Manalu, Janviter; Safanpo, Apolo; Karapa, Enos; Hartiningsih, Endang; Liga, Marthen; Wambrauw, Oscar O.; Silo, Akbar (Fakultas Teknik Universitas Pancasila, 2024)
Barapen, a cooking tradition in various indigenous Papuan communities. To date, various social science studies have been conducted to examine social values, business economics, and political economy. While research in the aspects of applied science has yet to be conducted to study the phenomenon of heat transfer by natural convection from hot stones to food in cooking packs, this research was conducted. The purpose of this research is to study the phenomenon of heat transfer by natural convection from hot stones to food in cooking packs. In this study, a square-shaped artificial pool (260 cm x 210 cm x 50 cm) with white batah stone walls was used to cook food in a barapen. On the four walls, a type K thermocouple is inserted to measure the temperature at 3 layers, which will be the object of research. The ingredients are vegetables, sweet potatoes, and chicken meat that has been cut and stoned. As a discussion, the temperature gradient between layers occurs due to the difference in the amount of volumetric heat against time in each layer. The difference in the amount of heat in each layer is due to the difference in the density of the hot vapor trapped in each layer. Thus, it can be said that the cooking of food in Barapen occurs due to natural heat convection.